Presentation - Hipólito, Rodrigo (Revista do Colóquio, 2024)
For this 23rd edition of Revista do Colóquio, we decided to resume receiving submissions with free themes. Until the previous issue, our editions opened calls with specific themes. As a consequence of these calls, some works that did not build a direct dialogue with the set of texts could only be published in subsequent editions. We understand that free calls allow for faster dissemination of research results. In addition to this gain, we can count on the positive side of unpredictability. The diversity of research objects and approaches to the field of arts can make each edition function as a set of doors for the most varied reading interests.